Fake news - Keppeler, Jill (Rosen verified: current issues, 2021)
"As news media has moved past established old-time sources and into new forms-and as the cry of "fake news" is used for both false sources and real news that people dislike-it becomes more and more difficult to know what to trust. In this informative book, readers will learn what clues and signs to watch for when reading, watching, or listening to news media. Useful tips will help them figure out when to look deeper on social media, and intriguing facts will give perspective to help them learn more about the role of the free press in U.S. society"--Provided by publisher.